The Cytotoxic Activity of Annona muricata Linn Leaves Ethanolic Extract (AMEE) on T47D Breast Cancer Cell Line - Soilia Fertilita; Willy Sandhika; Desak Gede Agung Suprabawati (Medical Laboratory Technology Journal, 2020)
Breast cancer is the most common cancer in women throughout the world, with new cases and deaths which continue to increase. Soursop leaves (Annona muricata L) have been used extensively in traditional medicine, including cancer. Acetogenin, alkaloids, and phenols contained in soursop leaves are known to have anti-cancer effects. Among them, acetogenin has the most dominant role and reported to have a cytotoxic effect on various cancer cell lines. This study aims to determine the cytotoxic activity of soursop leaf ethanol extract on T47D breast cancer cell line. Measurement of cytotoxic activity was carried out by the MTT method, and the viability percentage of T47D cells was calculated based on the absorbance values in the treatment, cell control, and media control groups of each replicate. The correlation between extract concentration and viability percentage of the T47D cell line was outlined in the regression equation to obtain the IC50 value. IC50 values of 109.91 ± 3.04 with R values 0.975 and R2 0.9508 obtained. R values close to 1 indicated a strong correlation between extract concentration and the percentage of living T47D cells. Meanwhile, the amount of R2 suggested that the level of AMEE had a 95.08% influence on the rate of cell viability, and the other 4.92% influenced by factors other than the AMEE dose. These results indicated that the ethanol extract of soursop leaves has a cytotoxic effect and has the potential to inhibit T47D cell proliferation in vitro.